Drosophila cacophony channels: a major mediator of neuronal Ca2+ currents and a trigger for K+ channel homeostatic regulation. - Peng, I.F.; Wu, C.F. (Journal of Neuroscience, 2007)
The cacophony (cac) locus in Drosophila encodes a Ca2+ channel alpha subunit, but little is known about properties of cac-mediated currents and functional consequences of cac mutations in central neurons. We found that, in Drosophila cultured neurons, Ca2+ currents were mediated predominantly by the cac channels. The cac channels contribute to low- and high-threshold, fast- and slow-inactivating types of Ca2+ currents, take part in membrane depolarization, and strongly activate Ca2+-activated K+ current [I(K(Ca))]. In cac neurons, unexpectedly, voltage-activated transient K+ current I(A) is upregulated to a level that matches I(K(Ca)) reduction, implicating a homeostatic regulation that was mimicked by chronic pharmacological blockade of Ca2+ currents in wild-type neurons. Among K+ channel transcripts, Shaker mRNA levels were preferentially increased in cac flies. However, Ca2+ current expression levels remained unaltered in several K+ channel mutants, illustrating a key role of cac in developmental regulation of Drosophila neuronal excitability.